Factors influencing the participation in IIUM Zero Single-Use Plastic Campaign - Nor Shafiqizni Yuhani,; Nur Ashikin Mohd Effendi,; Norsyaza Hanis Rushdan,; Farah Nadira Zamri,; Saodah Wok, (Penerbit Universiti Kebangsaan Malaysia, 2020)
IIUM Zero Single-Use Plastic Campaign was launched in February 2019, requiring everyone in IIUM not to use plastics including plastic straws, plastic bags, and plastic food containers. As such, this study attempted to gauge the IIUM community’s reception towards the Zero Single-Use Plastic Campaign. The objectives of this study are: (1) to determine the level of awareness, perception, attitude, readiness, and behaviour towards the Zero Single-Use Plastic Campaign; (2) to analyze the relationship among awareness, perception, attitude, readiness, and behaviour in the Zero Single-Use Plastic Campaign; and (3) to find out the best predictor of community behaviour towards such campaign. The study tested the theory of planned behaviour and employed a quantitative research design using the survey method with the questionnaire as its research instrument for data collection. A total of 398 respondents participated in the study. The results of the study show that there is a high level of awareness, perception, attitude, readiness, and behaviour towards the Zero Single-Use Plastic Campaign. Also, there are positive and significant relationships between the factors and behaviour (usage). Readiness is the best predictor of the zero single-use plastic usage. All the hypotheses are supported. Therefore, it can be concluded that the IIUM campus community supports the campaign. Hence, the theory of planned behaviour holds true and is supported by this study.